2019
DOI: 10.1016/j.ejphar.2019.03.054
|View full text |Cite
|
Sign up to set email alerts
|

Identification and biochemical analyses of selective CB2 agonists

Abstract: Cannabinoid CB 1 and CB 2 receptors are activated by Δ 9-tetrahydrocannabinol, a psychoactive component of marijuana. The cannabinoid CB 1 receptor is primarily located in the brain and is responsible for the psychoactive side effects, whereas the cannabinoid CB 2 receptor is located in immune cells and is an attractive target for immune-related maladies. We identify small molecules that selectively bind to the cannabinoid CB 2 receptor and can be further developed into therapeutics. The affinity of three mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…Although studies reported that activation of CB 2 can reduce pain through anti-inflammation [ 7 , 28 , 29 ], there is still no CB 2 -subtype selective agonist on the market. Previously, we identified a compound, ABK5, which was originally found to activate CB 2 in a high throughput screening [ 25 ], and to be a CB 2 -subtype selective agonist [ 23 ]. ABK5 inhibited IL-2 and TNF-α production in Jurkat cells and MOLT-4 cells, and mitigated inflammation in a Complete Freund’s adjuvant treated inflammatory pain model in rats [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although studies reported that activation of CB 2 can reduce pain through anti-inflammation [ 7 , 28 , 29 ], there is still no CB 2 -subtype selective agonist on the market. Previously, we identified a compound, ABK5, which was originally found to activate CB 2 in a high throughput screening [ 25 ], and to be a CB 2 -subtype selective agonist [ 23 ]. ABK5 inhibited IL-2 and TNF-α production in Jurkat cells and MOLT-4 cells, and mitigated inflammation in a Complete Freund’s adjuvant treated inflammatory pain model in rats [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…d N.D.: K i or EC 50 value was not determined. e Parameters of ABK5 were determined previously and are shown for comparison [ 23 ].…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations